(untitled) (Journal of Dhaka Medical College, 2015)
Context: Non Alcoholic Fatty liver disease (NAFLD) is a hepatic manifestation of metabolic syndrome. The pathogenesis of steatosis and cellular injury is thought to be related mostly to insulin resistance. Insulin sensitizing drugs showed promising results in number of trials. This was an open label clinical trial in newly detected glucose intolerant patients with NAFLD, to evaluate the effectiveness and superiority of pioglitazone and metformin combination to metformin alone. Methods: Forty nine patients with newly detected abnormal glucose tolerance, naïve to any anti diabetic drug, were randomly selected, from the gastroenterology out-patient department of BIRDEM Hospital, Dhaka, with the findings of ultasonographic changes of fatty liver and raised ALT and assigned to 6 months treatment with pioglitazone 30 mg plus metformin 1700 mg daily (Group 1, n=27) or only metformin 1700 mg alone (Group 2, n=22). Results: Mean age of the study population was 45.80±8.54 years, Male female distribution of the study subjects were 65.3% and 34.7% respectively. Significant reduction of ALT, F, ABF, HbA1c, cholesterol, triglyceride of the study population were achieved either by metformin alone or with combination after six months (visit 1 vs visit 3, ALT: 97.99+22. vs 55±17.49 u/ l; Fasting sugar: 9.1+1.9 vs6.64±0.94, mmol/l; ABF: 13.3±2.5 vs 8.69±1.21 mmol/l; HBA1c: 8.1±0.9 vs 6.87±0.57%; Cholesterol: 205.9±30.1 vs 186.12±22.26 mg/dl; TG: 230.4+48.1 vs 166.2±31.82). In comparison between two groups, Group 1 had found to be significantly better glycemic control compared to their counterpart at the end of 6 months (Group 1 vs Group 2, FBG: 6.37±0.56 vs 6.98±1.2; ABF: 8.34±0.84 vs 9.1±1.46; serum cholesterol, TG, and ALT levels were also found to be significant change as Cholesterol: 178.89±18.59 vs 195±23.55 mg/dl; TG: 155.85±20.99 vs 178.91±38.24 mg/ dl; ALT: 55±17.49 vs 45.74±12.63 u/L. In final visit, ultrasonographic change also found to be significantlyimproved from fatty change to normal in patients with both metformin and pioglitazone group than patients on metformin alone. Conclusion: Treatment of NAFLD of newly detected Type 2 DM or IGT patients with high ALT by both metformin and pioglitazone is more effective in reduction of ALT and lipids and also able to reverse the severity of fatty changes of liver towards normal significantly. DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21540 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 188-194